KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING UNTUK MOTIVASI, DISIPLIN, DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Fitriani, Nadea; Rochmatullah, Mahameru Rosy (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to explore the impact of motivation, discipline, and accounting information systems on employee performance, with job satisfaction serving as a mediating factor. The research sample consisted of employees from PT Tiga Serangkai Pustaka Mandiri Solo, totaling 105 participants. The analytical method utilized was Partial Least Squares (PLS) with the WarpPLS 7.0 software. The data analysis results demonstrate that both motivation and discipline have a significant impact on performance. Additionally, motivation and discipline positively impact job satisfaction, which in turn significantly influences employee performance. Keywords: Motivation; Discipline; Accounting Information System; Employee Performance; Job Satisfaction